Ageism, human rights and ethical aspects of end-of-life care for older people with serious mental illness - Kotzé, Carla; Roos, Johannes Lodewikus (Frontiers in Psychiatry, 2022)
The effects of ageism, preservation of human rights and dignity, supported or shared decision making, palliative approaches and other important ethical considerations are aspects that have to be taken into consideration during end-of-life care discussions and planning. This is especially important when vulnerable populations such as older individuals with serious mental illness are involved. This perspective article originated from a study where it was found that two thirds of 100 participants 60 years of age and older with serious mental illness had end-of-life decision-making capacity. This finding highlighted the individual and contextual nature of decision-making capacity, the importance of values and focus on the protection of human dignity during end-of-life discussions. Healthcare providers have a duty to initiate end-of-life and advance care discussions, to optimise decision-making capacity, and to protect autonomous decision-making. Chronological age or diagnostic categories should never be used as reasons for discrimination and all patients should where possible receive end-of-life care in keeping with their preferences and values.